2015
DOI: 10.1038/ncomms10170
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quasi-monoenergetic ion beams from laser-driven relativistic plasmas

Abstract: Table-top laser–plasma ion accelerators have many exciting applications, many of which require ion beams with simultaneous narrow energy spread and high conversion efficiency. However, achieving these requirements has been elusive. Here we report the experimental demonstration of laser-driven ion beams with narrow energy spread and energies up to 18 MeV per nucleon and ∼5% conversion efficiency (that is 4 J out of 80-J laser). Using computer simulations we identify a self-organizing scheme that reduces the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 65 publications
3
86
0
Order By: Relevance
“…These foils delivered narrow ion-energy peaks with relatively high laser-ion conversion efficiency and a smaller beam divergence (up to 17° HWHM) 48 . The dominant charge state was Al 11+ along with the ubiquitous proton beam from target-surface impurities and a small Al 12+ component.…”
Section: Laser-driven Intense Ion-beams With Narrow Energy Spreadsmentioning
confidence: 99%
“…These foils delivered narrow ion-energy peaks with relatively high laser-ion conversion efficiency and a smaller beam divergence (up to 17° HWHM) 48 . The dominant charge state was Al 11+ along with the ubiquitous proton beam from target-surface impurities and a small Al 12+ component.…”
Section: Laser-driven Intense Ion-beams With Narrow Energy Spreadsmentioning
confidence: 99%
“…19 Time-integrated measurement of ion spectra alone is insufficient to resolve the key underlying dynamics required to determine which mechanism dominates for given target and laser pulse parameters. Moreover, recent work has shown that multiple acceleration mechanisms can occur over the duration of the laser pulse interaction with an ultrathin foil target.…”
Section: Intra-pulse Transition Between Ion Acceleration Mechanisms Imentioning
confidence: 99%
“…Aluminum foil with proper thickness could be applied to spatially separate the ion trajectories of different species. 12 Alternatively, a pair of electrodes can be added to the 2DpWASto provide a transverse deflection which also spatially separates the proton and heavier ion tracks, just functions as a multi-pinhole TP-Spec. Fig.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…By replacing the pinhole with a slit or a row of pinholes, one-dimensional (1D) angular-resolved energy distributions of proton beams were measured. [9][10][11][12] This design was proposed to have imaging capability. 9 The energy spectrum, spatial distribution, and angular distribution of the proton beam were found to be inherently correlated with each other using the novel spectrometer design.…”
Section: Introductionmentioning
confidence: 99%